Patient participation in self-monitoring regarding healthcare of heart failure: an integrated systematic review - Sophia Olofsson; Hanna Josephsson; Maria Lundvall; Peter Lundgren; Birgitta Wireklint Sundström (BMC Primary Care)
Abstract Background Self-monitoring in cases of heart failure (HF) can lead to improved health and early detection of states of illness, potentially avoiding unnecessary hospitalisation. Legislation emphasizes the importance of patient participation in health care. This is possible and simplified due to the ongoing digitalisation within the healthcare system. The aim of this study was therefore to describe existing research knowledge on patient participation in self-monitoring regarding healthcare of HF, in the context of digitalisation of healthcare. Methods A systematic literature review with an integrative approach was conducted February 2021 (6 years) and April 2024 (9 years). The review consisted of 12 articles accumulated from four databases. The review was performed in line with the standards of the PRISMA statement, registration number: PROSPERO 2021:244,252. Results A total of twelve studies were included, both quantitative and qualitative research. The studies had a wide international spread and included a total of n = 1393 patients aged between 52–77 years, predominantly men. Various aspects of patient participation are the three themes: ‘Self-care ability’, ‘Interaction with healthcare professionals’, and ‘Empowerment and Individual preferences’. The results indicate that self-monitoring has a predominantly positive effect on self-care behavior and satisfaction with care. Increased awareness and confidence in patients´ own self-care abilities were reported especially in qualitative studies. Through the use of self-monitoring, information and knowledge about HF led to increased control of the disease. Additionally, differences between qualitative and quantitative studies are demonstrated even in this partial result. The qualitative studies showed an increased understanding of disease situations, but corresponding conformity is not shown in quantitative research, and an increased level of knowledge is not yet proven. Conclusions The fact that there is a lack of empirical data in this field of research and that the available data is not coherent indicates that additional studies are required. In step with increased digitalisation and that great responsibility is placed on patient participation, there is a demand for patient studies that embrace a pronounced patient perspective with individual components of self-monitoring.